Transcranial direct current stimulation for chronic headaches, a randomized, controlled trial - Hervik, Jill Angela; Vika, Karl Solbue; Stub, Trine (Frontiers in Pain Research, 2024)
Background and objectives Chronic headaches are a frequent cause of pain and disability. The purpose of this randomized trial was to examine whether transcranial direct current stimulation (tDCS) applied to the primary motor cortex, reduces pain and increases daily function in individuals suffering from primary chronic headache. Materials and methods A prospective, randomized, controlled trial, where participants and assessors were blinded, investigated the effect of active tDCS vs. sham tDCS in chronic headache sufferers. Forty subjects between 18 and 70 years of age, with a diagnosis of primary chronic headache were randomized to either active tDCS or sham tDCS treatment groups. All patients received eight treatments over four consecutive weeks. Anodal stimulation (2 mA) directed at the primary motor cortex (M1), was applied for 30 min in the active tDCS group. Participants in the sham tDCS group received 30 s of M1 stimulation at the start and end of the 30-minute procedure; for the remaining 29 min, they did not receive any stimulation. Outcome measures based on data collected at baseline, after eight treatments and three months later included changes in daily function, pain levels, and medication. Results Significant improvements in both daily function and pain levels were observed in participants treated with active tDCS, compared to sham tDCS. Effects lasted up to 12 weeks post-treatment. Medication use remained unchanged in both groups throughout the trial with no serious adverse effects reported. Conclusion These results suggest that tDCS has the potential to improve daily function and reduce pain in patients suffering from chronic headaches. Larger randomized, controlled trials are needed to confirm these findings. Trial registration The study was approved by the local ethics committee (2018/2514) and by the Norwegian Centre for Research Data (54483).